Allograft Chip Incorporation in Acetabular Reconstruction: Multiscale Characterization Revealing Osteoconductive Capacity. (3rd November 2021) - Butscheidt, Sebastian; von Kroge, Simon; Stürznickel, Julian; Beil, Frank Timo; Gehrke, Thorsten; Püschel, Klaus; Amling, Michael; Hahn, Michael; Rolvien, Tim
Abstract : Background: Impacted bone-grafting with morselized allograft chips is commonly used to reconstruct acetabular bone defects in revision total hip arthroplasty (THA). While the overall clinical outcome of this procedure is described to be excellent, the microstructural basis and histological determinants of allograft incorporation remained to be further elucidated. Methods: The acetabula of 23 individuals with documented previous use of allograft chips during revision THA were explanted post mortem. The time that the allografts were in situ averaged 10.3 ± 4.5 years (range, 1.2 to 19.8 years). The host bone (HB)-allograft bone (AB) interface was characterized using a suite of high-resolution (HR) imaging techniques including HR-peripheral quantitative computed tomography (HR-pQCT), histological analysis, cellular histomorphometry, and scanning electron microscopy. Results: AB could be identified in 16 of the 23 cases. The HB and AB showed overlap (i.e., ingrowth) in 91.3% of the total interface. The mean ingrowth was 2.2 ± 1.0 mm with a maximum of 4.7 ± 2.1 mm. The periphery of the AB showed a tight interconnection with the HB associated with increased bone remodeling indices and increased trabecular thickness. While no association between the time in situ and the ingrowth was observed, the bone defect area was positively associated with the thickness of a fibrosis layer separating the ingrowth zone from the AB. Conclusions: Allograft chips in revision THA form an adequate osseous foundation with successful incorporation through ingrowth of the HB (i.e., osteoconduction). While complete remodeling was not observed, larger defects were associated with fibrosis formation, which may compromise stability. Clinical Relevance: Our study provides the first systematic, multiscale long-term evaluation of chip allograft incorporation in revision THA to underscore its successful clinical use. As larger defects were associated with fibrous ingrowth, structural allografts may be superior for larger defects in terms of long-term outcomes.